How to be NICEr in treating osteoarthritis. Issue 11 (November 2018) - Conaghan, Philip
Current guidelines for the treatment of osteoarthritis involve exercise and lifestyle modifications as well as pharmaceutical therapeutics for effective pain management. Is this message reaching patients, and are they exercising enough?